AN ANALYSIS OF SUBORDINATE CONJUNCTION USED IN NOVEL “THE COMPLETE ALICE IN WONDERLAND” BY CARROLL LEWIS FOR CORPUS LINGUISTICS RESEARCH - Khusniyatu Zulaikha; Lilia Indriani (Faculty of Education and Teachers Training, 2024)
Academic writing often features complex language, with nominalization of a process where verbs and adjectives are turned into nouns, being a key characteristic. This study investigates the use of nominalization in academic abstracts to understand how this feature contributes to the density and formality of academic language. The research analyzes eight academic abstracts using both qualitative and quantitative methods through manual identification and categorization of nominalized forms. The findings reveal a high frequency of nominalization, indicating its significant role in shaping abstract structure and conveying complex ideas concisely. This suggests that nominalization is a vital tool for achieving the linguistic goals of academic writing, particularly in summarizing research effectively.